2000
DOI: 10.1159/000008224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bilateral Deep-Brain Stimulation on Oral Control of Patients with Parkinsonism

Abstract: We assessed the oral system of parkinsonian patients treated with bilateral chronic stimulation of the ventral intermediate nucleus of the thalamus (Vim), and of the subthalamic nucleus (STN) to compare the effects of these procedures on the articulatory organs. Force transducers were used to sample ramp-and-hold force contractions generated by the upper lip, lower lip and tongue at 1- and 2-newton target force levels, as well as maximal force. Fourteen healthy control subjects and 14 parkinsonian patients par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 21 publications
0
28
1
1
Order By: Relevance
“…In general, the effects of DBS closely parallel previous reports of the effects of dopaminergic medication. 55 In contrast to bilateral Vim DBS, 56 speech and handwriting 57 can be moderately improved in some patients [58][59][60] but not in others. Both rest and action tremors are almost totally abolished.…”
Section: Results Of Stn Dbsmentioning
confidence: 98%
“…In general, the effects of DBS closely parallel previous reports of the effects of dopaminergic medication. 55 In contrast to bilateral Vim DBS, 56 speech and handwriting 57 can be moderately improved in some patients [58][59][60] but not in others. Both rest and action tremors are almost totally abolished.…”
Section: Results Of Stn Dbsmentioning
confidence: 98%
“…Deep brain stimulation (DBS) of the thalamus was introduced to avoid the side effects 20,21 induced by the lesion, 22 but VIM stimulation has also been shown to induce a worsening of speech. 23 As stimulation parameters can be adjusted, exacerbation of dysarthria following VIM stimulation would generally not be severe. However, some speech impairment might be accepted by patients as a compromise for a better tremor control.…”
Section: Abstract: Levodopa (L-dopa) and Subthalamic Nucleus (Stn) Stmentioning
confidence: 99%
“…This finding may explain, why on average speech is not much improved with STN DBS, 7 although it has been shown that oral control is improved with STN DBS to a greater extent than with levodopa, 47 whereas it is worsened with Vim DBS. 48 However, in single patients, whose parkinsonian hypophonia is highly levodopa-sensitive, STN DBS may induce a major improvement in speech. 49 Worsening of speech related to STN DBS and especially with DBS outside of the STN has also been reported.…”
Section: Corticobulbar Fibersmentioning
confidence: 99%